Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006377.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of hyperthermia and radiation therapy for treating locally advanced cervical carcinoma

Abstract: The limited number of patients available for analysis, methodological flaws and a significant over-representation of patients with FIGO stage IIIB prohibit drawing definite conclusions regarding the impact of adding hyperthermia to standard radiotherapy. However, available data do suggest that the addition of hyperthermia improves local tumour control and overall survival in patients with locally advanced cervical carcinoma without affecting treatment related grade 3 to 4 acute or late toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
0
31
0
3
Order By: Relevance
“…In 2010, Lutgens et al [7] published a systematic review comparing the combined use of HT and RT with RT alone for treating locally advanced CC. They reported that RT combined with HT yielded superior local tumour control rates (RR, 0.56; 95% CI, 0.39-0.79; p < .001) and OS (HR, 0.67; 95% CI, 0.45-0.99; p ¼ .05) compared with those yielded by RT alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Lutgens et al [7] published a systematic review comparing the combined use of HT and RT with RT alone for treating locally advanced CC. They reported that RT combined with HT yielded superior local tumour control rates (RR, 0.56; 95% CI, 0.39-0.79; p < .001) and OS (HR, 0.67; 95% CI, 0.45-0.99; p ¼ .05) compared with those yielded by RT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia (HT) has also been shown to be effective in the treatment of CC [7]. Two randomised phase III trials comparing patient groups receiving radiotherapy (RT) or RT þ HT as a primary treatment for locally advanced CC showed higher complete response (CR) rates and better overall survival (OS) in the combination therapy group [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hyperthermia influences several molecular parameters involved in sensitizing tumor cells to radiation and can enhance the potential of targeted radiotherapy. Therefore, radiotherapy combined with hyperthermia may become a tool for local control of an inoperable tumor or an adjuvant therapy in the context of surgery [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia is a type of cancer treatment in which the body tissue is exposed to high temperatures to damage and kill cancer cells; it enhances the effect of radiotherapy and then allows radiation therapy to be performed at lower doses, reducing its side effects without reducing its effectiveness [12,13]. Radiation therapy combined with hyperthermia may become an important tool for the local therapy of unresectable osteosarcomas or an adjuvant treatment in the context of surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for locally advanced cervical cancer is external beam radiotherapy with image-guided adaptive brachytherapy [1,2] and concurrent chemotherapy [3,4] or hyperthermia [5]. More than 90% of patients show complete local response after such treatment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%